Estrategias publicitarias para la difusión de la fiesta en honor a la Virgen de Tránsito de la parroquia Totoras, cantón Ambato - Curay Chango, Jessica Nicole (2025)
This project focuses on addressing the issue of the limited promotion of the festivity in honor of the Virgin of Tránsito, celebrated in the Totoras parish, Ambato canton. This lack of awareness has significantly impacted the preservation of local cultural heritage and has jeopardized the continuity of this important tradition. Therefore, the primary objective is to enhance the recognition of the festivity through advertising strategies that boost tourism during the event and increase awareness among the target audience. To achieve this goal, a mixed methodology was implemented, integrating qualitative and quantitative approaches. This approach enabled a detailed analysis of the perceptions and level of knowledge of the community's residents regarding the social and cultura aspects of their locality. Market studies, along with audience segmentation, indicated that efforts should primarily focus on individuals aged 20 to 40, who represent a key group for revitalizing the festivity. The survey results and analysis confirm the need to implement effective actions. In this context, the creation of a representative graphic identifier and the execution of an advertising campaign are proposed, primarily focused on promoting the most relevant cultural events through social media, as current dissemination in these channels is insufficient. To ensure success, the collaboration of advertising experts was secured, in addition to the active participation of local organizers. This approach allowed the integration of authentic and enriching perspectives on the parish’s traditions. In this way, the project aims to spark interest and encourage the participation of the residents, fostering a sense of pride and belonging to their culture. Ultimately, it seeks to revitalize the festivity in honor of the Virgin of Tránsito, promoting its preservation as a cultural legacy of immeasurable value for future generations.